Depression and anxiety in patients with cancer - Nowicki, Andrzej; Rządkowska, Beata (Contemporary Oncology/Współczesna Onkologia, 2005)
Patients who suffer from cancer are particularly exposed to anxiety and depression. The reasons are both biological changes in the body and social factors. In spite of a large prevalence of these disorders only 20% of them are correctly diagnosed. The purpose of this paper was the evaluation of the intensity of anxiety and depression among patients with cancer as well as evaluation whether social and demographic factors have an influence on the intensity of anxiety and depression. The group of 100 people has been examined. Cancer has been diagnosed during the last half a year among those patients. I used a personally prepared questionnaire, partly based on the Beck’s Depression Scale. The research proved that 91% of patients suffered from anxiety because of cancer and 41% of them had the symptoms of depression. The anxiety and depression as a real problem for patients with cancer was proved. The reasons of anxiety are connected to cancer. The statistical analysis showed that the intensity of anxiety and depression depends on such factors like having children, husband and education